Memorandum of Understanding between the International Livestock Research Institute (ILRI) and Assosa University - International Livestock Research Institute; Assosa University (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Memorandum of understanding (MoU) between the International Livestock Research Institute (ILRI) and Assosa University. On March 11, 2022, MoU was signed by Jimmy Smith, Director-General of ILRI, and Haimanot Dissassa, Vice-President of Assosa University.